Skinny as a Bird: Design fiction as a vehicle for reflecting on food futures. (August 2022) - Hebrok, Marie; Mainsah, Henry
Abstract: This article explores the use of design fiction as a vehicle for critically reflecting on the complex issue of sustainable food consumption and production. The paper presents the design fiction Bird, a food delivery service that provides food rations to its customers based on their exact nutritional needs and self-improvement goals. The service makes food consumption sustainable by design, leveraging individual lifestyle ambitions to circumvent the need to translate sustainability awareness into action. We discuss what it means to embed provocation, critique, and reflection in a design fiction that highlights potential preferable and non-preferable trajectories of change related to imaginaries of technocentric food futures. Through a design fiction artefact that reflects a complex set of ethical, social, cultural, political, and environmental issues related to food consumption, the aim is to examine how design fiction can serve as an entry point for imagining and critiquing possible futures. Highlights: Demonstrating design fiction as a useful entry point for: Imagining and critiquing possible futures in the context of sustainable food consumption. Expand the way we think about sustainable food futures – beyond the incremental improvements. Help us project into a possible future in which current food practices have become transformed.